INITIATIVES OF PUNJAB GOVERNMENT TO PROMOTE FEMALE EDUCATION: AN EVALUATIVE STUDY - Budhia, Divya; Kaur, Tushinder Preet (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Women in Punjab state have to face discrimination not only on grounds of education, but in almost every field of life so much so that they are denied their right to take birth. In such circumstances, importance of female education increases manifold as education among women will make women more aware, independent and empowered. State government is making noteworthy efforts to promote female education and bring about equality in the society. Present study attempts to evaluate initiatives undertaken by the Punjab government to promote female education. The study highlights the achievements and loopholes of the existing schemes and also offers useful suggestions that will set the ground for further policy initiatives.